Antioxidant enzymes activity during age polyethism in Apis mellifera L., 1758. Issue 5 (20th October 2021) - Sagona, Simona; Betti, Laura; Casini, Lucia; Palego, Lionella; Giannaccini, Gino; Felicioli, Antonio
Abstract : Temporal polyethism is based on physiological differences related to the honey bee activities into the colony, suggesting a different requirement of antioxidant activity in each honey bee development stage. The superoxide dismutase (SOD), the catalase and the glutathione S transferase (GST) activities were investigated in ventriculus, thorax and wings of pupae with dark brown eyes newly emerged, nurse, guardian and forager bees. SOD activity resulted significantly higher in ventriculus of newly emerged bees than the others investigated development stages, while in the thorax, newly emerged and guardian bees reported significantly higher SOD activity than pupae in dark brown eyes stage, nurses and forager bees. No, statistically differences in catalase activity resulted among honey bee ages. In pupae, nurse, guardian, and forager bees, GST activity resulted higher in the wings than in the other honey bee organs. Further investigations are desirable to clarify the distribution of the antioxidant enzymes in the different organs of the honey bee.